Análisis de las necesidades de capacitación a los prestadores turísticos del Cantón Ventanas - PAZOS VALLEJO, WASHINGTON STEVEN (2024)
Tourism training is of great interest in this sector, in order to increase the activity and competitiveness of the establishments in the Ventanas Canton. The objective of this research was to identify the training needs of tourism providers in this area, to promote the improvement of the quality of services. An exploratory research methodology was used, with a quantitative approach, allowing the use of the method for convenience, managing to survey 20 tourist establishments in this town. Where eighty-five percent of those surveyed stated that they would always agree to provide training to their staff, while fifteen percent indicated that it is sometimes necessary to improve the quality of their services and the performance of their workers. Therefore, service providers are recommended to manage a training plan aimed at their staff to improve the quality of the service that covers; customer service training, etiquette and protocol training, food and beverage training, first aid training, and cultural awareness training. Managing to increase tourism development in this City.